Adult growth hormone deficiency in CEE region: Heterogeneity of the patient pathway. (June 2019) - Shimon, Ilan; Badiu, Corin; Bossowski, Artur; Doknic, Mirjana; Dzivite-Krisane, Iveta; Hána, Václav; Kollerova, Jana; Natchev, Emil; Pfeifer, Marija; Szũcs, Nikolette; Hey-Hadavi, Juliana; Gomez, Roy
Abstract: Objectives: Adult growth hormone deficiency (AGHD) is a rare disease characterised by abnormal body composition, reduced strength and exercise capacity and impaired psychological wellbeing. An advisory board of leading Central and Eastern European (CEE) endocrinologists was assembled to gain insights into the status of AGHD care in the CEE region. Topics of discussion included the position of adult hypopituitarism/AGHD in health system priorities, availability and affordability of treatments, awareness of AGHD, practice guidelines used in CEE countries and provisions for long-term care of patients. Design: Prior to the meeting, the advisors were asked to summarise, using an itemised survey questionnaire, the usual standards of care for patients with AGHD in their country. At the meeting, the panel of experts discussed the findings and thereby elucidated similarities and differences among CEE countries; these were compared with international guideline-recommended practices for AGHD. Results: All CEE countries involved reported having some type of infrastructure in place for care of patients with GHD transitioning from adolescence to adulthood. Most countries reported having at least one specialist centre for patients with AGHD. The main variations across the region included initial entry into healthcare systems, tests required to confirm AGHD diagnosis and medication reimbursement by health authorities. Most CEE countries relied on international society-led guidelines, while some countries have developed national guidelines. Conclusion: The CEE Adult Endocrinology Advisory Board meeting recognised considerable diversity in the care and patient pathways for AGHD across CEE countries. Additional work is needed to optimise care of patients with AGHD in the CEE region. Highlights: Management of adult growth hormone deficiency varies across Central & Eastern Europe. Variations in local treatment practices, diagnostic assessments and reimbursement. Recommendations for patient referral, evaluation and management are provided. Education on AGHD for healthcare providers and patients would be beneficial.